Is central repair with coronary artery bypass grafting enough for multi-organ malperfusion in acute type A aortic dissection with coronary malperfusion? - Naoshi Minamidate; Hodaka Wakisaka; Kohei Hachiro; Fumihiro Miyashita; Masanori Morimoto; Yasuo Kondo; Masahide Enomoto; Noriyuki Takashima; Tomoaki Suzuki (Asian Journal of Surgery, 2023)
Objectives: Acute type A aortic dissection with coronary malperfusion syndrome is rare but associated with high mortality. Multi-organ malperfusion is an independent predictor of acute type A aortic dissection. Coronary malperfusion requires treatment, but it is not feasible to treat all malperfusions. The adequacy of “central repair and coronary artery bypass grafting” for patients with coronary and other organ malperfusion is unknown. Methods: Of the 299 patients who underwent surgery between 2008 and 2018, 21 patients with coronary malperfusion, who received cental repair with coronary artery graft bypass, were analyzed retrospectively. They were divided; into Group M (n = 13, coronary and other organ malperfusion) and Group O (n = 8, coronary malperfusion only). The patient background, surgical content, details of malperfusion, surgical mortality and morbidity, and long-term outcome were compared. Results: There was no difference in operation time (205 ± 30 vs. 266 ± 88, p = 0.49), but the time from arrival to circulatory arrest tended to be shorter in Group M (81 vs. 134, p = 0.05). Among Group M, cerebral malperfusion was the most common at 92%. Two of the three cases with mesenteric malperfusion died. The mortality of Group M and Group O was 13% and 15% (P = 0.85), respectively. There was no difference in long-term mortality (p = 0.62). Conclusions: Central repair and coronary artery bypass grafting is a sufficiently acceptable treatment for patients with acute type A aortic dissection and multi-organ malperfusion, including coronary malperfusion.